2015
DOI: 10.1103/physrevc.91.029901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Coarse-grained potential analysis of neutron-proton and proton-proton scattering below the pion production threshold [Phys. Rev. C88, 064002 (2013)]

Abstract: In our recent paper, we presented a fit to neutron-proton and proton-proton scattering data below the pion production threshold. A new data selection process was used to obtain the largest mutually consistent database from all data reported during the years 1950-2013. However, the provided information was not enough to reconstruct the full database.In Tables II and III we list the total measurements n i and the final number o f measurements actually used in the fit «2 for pp and np data, respectively. For some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
152
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(157 citation statements)
references
References 30 publications
5
152
0
Order By: Relevance
“…[22]. In the past, several strategies have been pursued: extractions from πN scattering data, either in terms of phase shifts [11,23] or cross sections [24], determinations from N N observables [25,26], or a combination of both [27]. Moreover, in [9] the matching with a reconstructed dispersive πN amplitude was performed in the subthreshold region where ChPT is expected to converge best, but the extrapolation from the physical region still required input from πN data (similarly, while starting from the subthreshold region, the LECs are determined from fits to phase shifts in [13]).…”
Section: Introductionmentioning
confidence: 99%
“…[22]. In the past, several strategies have been pursued: extractions from πN scattering data, either in terms of phase shifts [11,23] or cross sections [24], determinations from N N observables [25,26], or a combination of both [27]. Moreover, in [9] the matching with a reconstructed dispersive πN amplitude was performed in the subthreshold region where ChPT is expected to converge best, but the extrapolation from the physical region still required input from πN data (similarly, while starting from the subthreshold region, the LECs are determined from fits to phase shifts in [13]).…”
Section: Introductionmentioning
confidence: 99%
“…2 This self-consistency condition, which can only be checked a posteriori and entitles legitimate error propagation, has usually been overlooked in the NN literature. In [22] a few of these tests are reviewed along with a recently proposed Tail-Sensitive test [23] and it was found that the three potentials DS-OPE [17], DS-χTPE [24] and Gauss-OPE [22] have standard normal residuals. The three more recent potentials DS-Born, Gauss-χTPE and Gauss-Born also were found to have normally distributed residuals [25].…”
Section: Description Of Nn Scattering Errorsmentioning
confidence: 99%
“…The fit requires a total of 46 parameters and yields χ 2 /d.o.f. = 1.04 to the self-consistent data base [17,19].…”
Section: Description Of Nn Scattering Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent analysis [11,12] accomplished a 3σ -selfconsistent selected pp+np database involving 6713 data and normalizations in the LAB energy range between 1 eV for np and 338 KeV for pp and a maximum of 350 MeV for both np and pp 1 . This has lead to the new 6 Granada potentials denoted as DS-OPE [11,12], DS-χTPE [13,14], SOG-OPE [15], SOG-χTPE, DS-∆BO and SOG-∆BO [16].…”
Section: Introductionmentioning
confidence: 99%